MARKETING STRATEGIES IN OUTDOOR ADVERTISING: TRICKS OF MARKETERS - OVERVIEW AND ANALYSIS OF THE MAIN - TSIVAK, Volodymir (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This article examines the main marketing strategies used in today’s outdoor advertising, and also reveals and analyzes the tricks and techniques that marketers use to effectively attract the attention of consumers. The modern advertising market requires marketers to constantly increase their creativity and ingenuity. The following key aspects are considered in the article: One of the ways to attract the consumer’s attention is to use emotional aspects in advertising. The article analyzes in detail how marketers create advertising campaigns aimed at evoking specific feelings and emotions in the target audience. Referring to examples of successful advertising campaigns, the article analyzes how marketers create memorable images and meaningful symbols that contribute to increasing brand recognition. Marketers actively use sociocultural trends, events and symbols in advertising to strengthen the perception of their product or service in society. The article analyzes how this happens and what examples can be given. Modern technological solutions and innovations in the field of advertising are reviewed, such as the use of virtual reality, interactive advertising formats, etc. Through a detailed analysis of these aspects, the article aims to understand how marketers create successful advertising campaigns and use different strategies to achieve their goals in today’s market. It will help both specialists in the field of marketing and everyone who is interested in the marketing aspects of outdoor advertising.